1993
DOI: 10.1073/pnas.90.5.1952
|View full text |Cite
|
Sign up to set email alerts
|

Developmental expression of the platelet-derived growth factor alpha-receptor gene in mammalian central nervous system.

Abstract: We recently reported that the platelet-derived growth factor (PDGF) A-chain gene is highly exp e in neurons of embryonic and adult mouse central nervous system and suggested that its secretion by neurons may support development and maintenance of gla. We have now analysed the levels and sites of expression of the cognate PDGF a-receptor gene in brain and spinal cord ofembryonic and adult mice by in situ hybridization. The predominant cell populations in both gray and white matter expressing rpts of the PDGF a-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
48
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 73 publications
(54 citation statements)
references
References 21 publications
6
48
0
Order By: Relevance
“…42 PDGF is a critical regulator of gliomagenesis and neurogenesis and regulates tumor cell proliferation, migration, and angiogenesis. 43,44 Our data identify miR-134 as a mediator of the effects of multiple RTKs 23,24 This poses a major hurdle for a personalized medicine approach that aims at inhibiting RTK activation in GBM. Our data suggest that this hurdle might be potentially overcome by the use of the common RTK mediator miR-134.…”
Section: Discussionmentioning
confidence: 99%
“…42 PDGF is a critical regulator of gliomagenesis and neurogenesis and regulates tumor cell proliferation, migration, and angiogenesis. 43,44 Our data identify miR-134 as a mediator of the effects of multiple RTKs 23,24 This poses a major hurdle for a personalized medicine approach that aims at inhibiting RTK activation in GBM. Our data suggest that this hurdle might be potentially overcome by the use of the common RTK mediator miR-134.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that PDGF-AA drives certain events during embryogenesis, and also that there is a shift from an autocrine to a paracrine relationship during the development of the mouse embryo (41). Furthermore, expression of PDGF-AA mRNA in neurons and the ␣PDGFR message in glial cells has been shown to be developmentally regulated (66,67). A series of elegant studies examining the role of PDGF-AA (and thus the ␣PDGFR) in the development of the rat optic nerve indicate that PDGF-AA regulates differentiation of the O2A progenitor cells and acts as a survival factor (2,40,44,45).…”
mentioning
confidence: 90%
“…The expression of both PDGF receptors, PDGFR-a and -b, has also been demonstrated in neurons (Smits et al, 1991;Yeh et al, 1993;Vignais, et al, 1995). It has been shown that the expression of PDGF-B/c-SIS and PDGFR-b in injured brain increases after injury in both human and experimental rat brains.…”
Section: Introductionmentioning
confidence: 99%